2017
DOI: 10.7213/academica.15.s02.2017.a08
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios reprodutivos em cabras leiteiras e impactos potenciais nos sistemas de produção

Abstract: A exploração de caprinos leiteiros é uma importante atividade pecuária, com maior intensidade em algumas regiões do Brasil. A eficiência desta exploração está relacionada a vários fatores, sendo fortemente dependente dos índices reprodutivos. Os distúrbios reprodutivos estão mais relacionados a sistemas de produção intensivos e que exploram as principais raças leiteiras criadas no Brasil, sobretudo na região Sudeste do país. Basicamente, estes distúrbios podem ser diagnosticados por meio do exame clínico em as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…The results obtained support the information already described by Maia et al, (2017), who mentioned that cyclicality is also strongly influenced by breed origin, where Brazilian adapted goat/sheep exhibit reproductive activity throughout all the year. Even in areas close to the tropics, exotic breed sheep exhibit seasonality, as a consequence of the original local of breed effect.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained support the information already described by Maia et al, (2017), who mentioned that cyclicality is also strongly influenced by breed origin, where Brazilian adapted goat/sheep exhibit reproductive activity throughout all the year. Even in areas close to the tropics, exotic breed sheep exhibit seasonality, as a consequence of the original local of breed effect.…”
Section: Resultssupporting
confidence: 90%
“…Animal Sciences, v. 45, e57518, 2023 However, as the equator tropic is approached, reproductive seasonality is reduced, because the days are practically the same as the nights throughout the year. Thus, in subequatorial areas, such as the Brazilian Midwest, as long as there is nutritional support in sufficient quantity and quality, the ewe will manifest estrus throughout the year (Maia et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Cattle reproduction is also influenced by luminosity (Dahl et al, 2010). Maia et al (2017) found that females exposed to a greater number of light hours per day reach puberty at a younger age compared to females exposed to fewer light hours. In agreement, Barcellos et al (2003) state that heifers kept under long days reach puberty earlier than those kept under short days, usually around one month, this stemming from the greater release of luteinizing hormone (LH) in response to estradiol.…”
Section: Introductionmentioning
confidence: 92%
“…Even with these characteristics, they are widely used due to the excellent milk production. However, several factors can influence this type of production, including reproductive and nutritional efficiency [15].…”
Section: Introductionmentioning
confidence: 99%